An integrated approach to training core stability - Gamble, P. (Strength and Conditioning Journal, 2007)
Despite the widespread popularity and application of core training, confusion remains regarding the precise performance benefits of and optimal approach to training the core. This article attempts to resolve the components that comprise lum-bopelvic stability and suggests an approach to training each element in an integrated fashion.